NOZGEKA—a collaborative curriculum development process for a Master of Science in Public health with a focus on infectious diseases epidemiology in Malawi: a perspective - John L. Z. Nyirenda; Balwani C. Mbakaya; Dirk Wagner; Katarina Stete; Veronika K. Jaeger; Antonia Bartz; André Karch; Esther Nanyinza; Margret Soko; Nathaniel Chimbatata; Griphin B. Chirambo; Berit Lange (Humanities & Social Sciences Communications)
Abstract NOZGEKA, meaning “PREPAREDNESS,” is a consortium comprising five research and higher education institutions: three from Germany and two from Malawi. The programme is implemented at the University of Livingstonia and Mzuzu University in Malawi, in collaboration with the Helmholtz Centre for Infection Research, the University of Münster, and the University Medical Centre Freiburg in Germany. The pandemic preparedness “NOZGEKA” project aims to contribute to building capacity with a focus on both public health surveillance and infectious disease epidemiology by establishing a sustainable and advanced post-graduate educational option in Malawi. Therefore, this perspective paper describes the collaborative process and administrative feasibility of developing a joint curriculum for a Master of Science in Public Health with a focus on infectious disease epidemiology (MSPE) in Malawi. Following a consultative process, an official kick-off meeting, regular meetings in small groups, and workshops, the consortium developed the full curriculum of the new MSPE including 16 modules during June 2023–December 2023, and in April 2024, we piloted two short-courses in Malawi. These short courses were clinical basics (22 participants including 12 females and 10 males) and mathematical modelling (22 participants including 5 females and 17 males). In December 2024, the National Council of Higher Education (NCHE) in Malawi registered the programme. At the beginning of 2025, we recruited the first cohort of 21 students, and teaching started in March 2025.